Lesotho : Development in a Challenging Environment - Hassan, Fareed M.A. (Washington, DC: World Bank, 2013)
The report reviews the Bank's development assistance to Lesotho, a poor country, of predominantly rural populations, landlocked and completely surrounded by, and economically dependent on, South Africa. Not surprisingly, a major development challenge for the country is that half the population lives below the poverty line, and income inequality is among the highest in the world. Other challenges are low quality of education, and health services, widespread HIV/AIDS, weak institutions, and lagging private sector development. Given the circumstances, Bank assistance evolved from an emphasis on stabilization and growth, to a focus on poverty reduction and private sector development towards the end of the 1990s. Throughout this period, the Bank supported joint work with the Government, and the International Monetary Fund on successive Policy Framework Papers, as well a Poverty Assessment, and a Strategic Economic Options Report; regrettably, other analytical work was not fully completed, and, notably absent were periodic reviews of public expenditures. Although the Lesotho Highlands Water Project (LHWP) featured substantial macroeconomic impact, serving as a catalyst in securing external financing, the Bank did not provide adequate technical support. The Bank assistance is rated as moderately satisfactory, institutional development as modest, with an uncertain sustainability, since growth has depended on aid inflows, linked to the LHWP, but which is likely to decline. Recommendations suggest a continued assistance, centered on poverty reduction, focusing on the quality of education, and human capital development.